Begonia ufoides (sect. Coelocentrum, Begoniaceae), a new species from limestone areas in central Guangxi, China - Qin, Yong-Hua; Liang, Yong-Yan; Xu, Wei-Bin; Lin, Che-Wei; Peng, Ching-I (Phytotaxa, 2017)
A peltate-leaved species of Begonia was recently collected from a limestone hill in central Guangxi, China. Based on a careful study of literature, herbarium material, and plants both in the wild and in cultivation reveals that it is a new species of Begonia sect. Coelocentrum, which we hereby describe as B. ufoides. In addition to a full taxonomic account, color plates and line drawings are provided to aid in identification. Begonia ufoides may be confused with B. umbraculifolia Y. Wan & B.N. Chang in southwestern Guangxi and B. phuthoensis H.Q. Nguyen in northern Vietnam, both of which are peltate-leaved calciphilous species in sect. Coelocentrum, but the new species  is clearly distinguishable in many morphological characters. A table comparing salient features of the three species is presented.